The impact of CEO duality and financial performance on CSR disclosure: Empirical evidence from state-owned enterprises in China - Cosmina Lelia Voinea; Fawad Rauf; Khwaja Naveed; Cosmin Fratostiteanu (Journal of Risk and Financial Management, 2022)
This paper studies the effects of a firm's financial performance (FP) and chief executive officer's (CEO) duality on the quality of corporate social responsibility (CSR) disclosure in the context of state-owned enterprises (SOEs) among Chinese A-share-registered companies. The results depict a negative relationship between CEO duality and CSR disclosure. Our results demonstrate that better-performing firms disclose CSR information more frequently and of higher quality compared with firms with poor financial performance. This role of financial performance in the quality of CSR disclosure is generally valuable in public enterprises; however, it is relatively sluggish in state-owned enterprises the outcomes indicate that the dual leadership structure reduces assessments and renders CEOs less liable to their stakeholders. Therefore, this study offers valuable information and details for regulators to improve corporate governance and CSR from the perspective of stakeholder theory.
Keywords: 330; financial performance (FP); corporate social responsibility (CSR) disclosure; CSR reports; chief executive officer (CEO) duality; state-owned enterprises (SOEs); dual leadership structures